Flux-Balance Modeling of Plant Metabolism - Sweetlove, Lee J.; Ratcliffe, R. George (Frontiers in Plant Science, 2011)
Flux-balance modelling of plant metabolic networks provides an important complement to 13C-based metabolic flux analysis. Flux-balance modelling is a constraints-based approach in which steady-state fluxes in a metabolic network are predicted by using optimisation algorithms within an experimentally bounded solution space. In the last two years several flux-balance models of plant metabolism have been published including genome-scale models of Arabidopsis metabolism. In this review we consider what has been learnt from these models. In addition, we consider the limitations of flux-balance modelling and identify the main challenges to generating improved and more detailed models of plant metabolism at tissue- and cell-specific scales. Finally we discuss the types of question that flux-balance modelling is well suited to address and its potential role in metabolic engineering and crop improvement.